Assessing the pry-out resistance of open rib shear connectors in cracked concrete – Engineering model with aggregate interlock. (1st October 2017) - Classen, Martin; Hegger, Josef
Highlights: Phenomenology of composite dowels' pry-out failure is investigated by shear tests. Development of mechanical engineering model for pry-out of composite dowels in cracked concrete. Validation of engineering model by experimental results. Conversion of engineering model to the design load level. Pre-estimating the impact of concrete cracking for different types of composite sections. Abstract: In steel and concrete composite structures, an efficient type of open rib shear connector, the so called composite dowel connector, can be used to transfer shear forces between the concrete slab and the steel section. In regions with negative bending moment, where concrete cracking occurs, the shear capacity of composite dowels with pry-out failure is significantly reduced. Concrete cracks appear as discrete discontinuities in the pry-out cone, which induce a pry-out cone detachment. In the cracks, the shear stress transfer is restricted to aggregate interlock. So far, the well-known design models do not account for concrete cracking. Therefore, they usually overestimate the composite dowels' shear resistance in cracked concrete. To resolve that structural safety deficit, the present article proposes a mechanical model for the assessment of the pry-out resistance of composite dowels. The novel approach can be applied to cracked and uncracked concrete slabs and shows good agreement with experimental investigations. The model is validated by a test data base and afterwards converted to the design load level. In the future, the approach can be assigned to other types of shear connectors, for example to fasteners and headed studs in cracked concrete.